Biomaterials for Local, Controlled Drug Delivery to the Injured Spinal Cord - Ziemba, Alexis M.; Gilbert, Ryan J. (Frontiers in Pharmacology, 2017)
Affecting approximately 17,000 new people each year, spinal cord injury (SCI) is a devastating injury that leads to permanent paraplegia or tetraplegia. Current pharmacological approaches are limited in their ability to ameliorate this injury pathophysiology, as many are not delivered locally, for a sustained duration, or at the correct injury time point. With this review, we aim to communicate the importance of combinatorial biomaterial and pharmacological approaches that target certain aspects of the dynamically changing pathophysiology of SCI. After reviewing the pathophysiology timeline, we present experimental biomaterial approaches to provide local sustained doses of drug. In this review, we present studies using a variety of biomaterials, including hydrogels, particles, and fibers/conduits for drug delivery. Subsequently, we discuss how each may be manipulated to optimize drug release during a specific time frame following SCI. Developing polymer biomaterials that can effectively release drug to target specific aspects of SCI pathophysiology will result in more efficacious approaches leading to better regeneration and recovery following SCI.